2013
DOI: 10.1109/tap.2013.2271493
|View full text |Cite
|
Sign up to set email alerts
|

Wideband 400-Element Electronically Reconfigurable Transmitarray in X Band

Abstract: A fully electronically reconfigurable 400-element transmitarray is studied numerically and experimentally in Xband. The array operates in linear polarization and consists of 20×20 unit-cells. A 1-bit phase resolution has been selected for the unit-cell in order to reduce the complexity of the biasing network and steering logic, the insertion loss and the overall cost of the antenna system. The unit-cell stack-up is simple and is made of four metal layers: active side, biasing lines, ground plane and passive si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 257 publications
(112 citation statements)
references
References 34 publications
1
107
0
Order By: Relevance
“…The considered multi-antenna systems are composed of a focal source illuminating a planar array constituted of blocks called unit-cells. To achieve high directivity for personal radar applications, it has been shown that TAs with 400 elements are a good choice [5], [14], [16]. Consequently, we considered 20 × 20 unit-cells each with size of 2.5 × 2.5 mm 2 (i.e.…”
Section: A Massive Array Characteristicsmentioning
confidence: 99%
“…The considered multi-antenna systems are composed of a focal source illuminating a planar array constituted of blocks called unit-cells. To achieve high directivity for personal radar applications, it has been shown that TAs with 400 elements are a good choice [5], [14], [16]. Consequently, we considered 20 × 20 unit-cells each with size of 2.5 × 2.5 mm 2 (i.e.…”
Section: A Massive Array Characteristicsmentioning
confidence: 99%
“…Nowadays, several studies are focusing towards the miniaturization and the adoption of large scale arrays [1] for several ranging and localization applications, such as mobile communication [2], simultaneous localization and mapping (SLAM) [3], [4] or personal radars [5], thanks to the possibility to achieve a precise and high-scanning resolution given by the large number of adopted antennas [6]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…A triple-layer transmitarray antenna is designed in [6], which achieves high gain of 28.9 dB at 11.3 GHz and bandwidths of 9% for 1-dB gain. Another approach is receiver-transmitter designs [10][11][12][13]. In this approach, a transmitarray antenna typically consists of two planar arrays of printed-type elements.…”
Section: Introductionmentioning
confidence: 99%